Correlação entre condições de saneamento básico e parasitoses intestinais na população de Assis, Estado de São Paulo - Ludwig, Karin Maria [UNESP]; Frei, Fernando [UNESP]; Alvares Filho, Firmino [UNESP]; Ribeiro-Paes, João Tadeu [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 1999)
Foi estudada a distribuição dos enteroparasitos mais freqüentes na população de Assis, São Paulo, de 1990 a 1992. Foram analisados 18.366 exames oriundos de seis postos de atendimento sanitário (PAS): Vila Marialves, Vila Progresso, Centro, Vila Xavier, Vila Fiúza e Vila Bonfim. A prevalência de enteroparasitoses geral foi 23,3%. Os enteroparasitos mais encontrados foram: Giardia intestinalis (8,7%), Ascaris lumbricoides (5,5%), Trichuris trichiura (2,4%) e Hymenolepis nana (1,9%). Na Vila Marialves, região de baixo nível sócio-econômico essas freqüências foram, respectivamente: 17%; 13,1%; 5,9% e 4,2%. A faixa etária 3 a 12 anos apresentou maior número de indivíduos parasitados. Estabeleceu-se uma correlação entre as condições de saneamento básico, expressos pelo número de ligações de água e esgoto, e a freqüência de parasitoses. Houve queda na freqüência de parasitoses nos PAS entre 1990 e 1992, coincidindo com o aumento do número de ligações de água e esgoto nestas regiões.

The distribution of the most frequent enteroparasites in the population of Assis, State of São Paulo, was studied from 1990 to 1992. A total of 18,366 medical examinations from six sanitary care centers in the neighbourhoods of Marialves, Progresso, city center, Xavier, Fiúza and Bonfim were analized. The general prevalence of enteroparasites was 23.3%. The most frequently found enteroparasites were: Giardia intestinalis (8.7%), Ascaris lumbricoides (5.5%), Trichuris trichiura (2.4%) and Hymenolepis nana (1.9%). In Marialves, a low income neighborhood, the prevalences were: 17%; 13.1%; 5.9% and 4.2%, rspectively. The age group from 3 to 12 years showed the largest number of infected individuals. There was a correlation between basic sanitation conditions, expressed as the number of places connected to the city water and sewage systems, and the prevalence of parasites. There was also a decrease of parasite prevalence in all sanitary care centers from 1990 to 1992, which coincided with the increase in the number of new water and sewage systems in these neighborhoods.
Correlation between sanitation conditions and enteroparasitoses in the population of Assis, São Paulo State, Brazil
Keywords: Enteroparasitoses; Prevalência; Saneamento básico; Epidemiologia; Enteroparasitosis; Prevalence; Sanitation; Epidemiology